UDK 677.051 RESEARCH ON THE OPTIMIZATION OF THE SAW GIN’S ROLL BOX - Umarov, Akmal (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Abstract: The improvement of saw gin machines, particularly their roll boxes, plays a crucial role in increasing the efficiency of cotton processing in the textile industry. The density of the seed roll inside the roll box directly affects productivity, energy consumption, and the degree of fiber damage. Numerous studies indicate that when density exceeds the optimal range of 325-550 kg/m3, the fiber quality deteriorates and machine productivity decreases. Therefore, modern engineering solutions, such as the introduction of accelerators, modified saw cylinders, and lifting mechanisms, have been proposed to regulate density and stabilize the ginning process. This paper presents a comprehensive analysis of structural modifications, operational parameters, and mechanisms applied in modern saw gin machines. Various types of accelerators – disk, blade, and elastic systems – are evaluated in terms of their contribution to fiber quality improvement and energy efficiency. Additionally, the role of automation, including pneumatic lifting devices and sensor-based control systems, is discussed as a means to optimize machine performance. The results demonstrate that the application of innovative accelerators, optimized saw parameters, and pneumatic mechanisms contributes to reducing fiber damage, stabilizing throughput, and increasing overall productivity. The research findings are expected to provide a theoretical and practical foundation for the development of advanced gin machine designs suitable for Uzbekistan’s cotton industry.